TERAPI PSIKORELIGIUS DALAM MENGATASI DEPRESI NEUROTIK (STUDI ANALISIS PEMIKIRAN DADANG HAWARI) - Indryani Puspita Sari; Abdur Razzaq; Manah Rasmanah (CONS-IEDU, 2023)
The highest incidence of depression is currently found in Southeast Asia, one of which is neurotic depression. Neurotic depression has a bad impact on a person's mental health so that it can cause changes in thoughts, feelings, behavior and physical health in individuals, but sufferers are still able to assess reality, self-understanding well and sufferers do not have characteristics of severe mental disorders (psychosis). This article aims to explain how psychoreligious therapy in overcoming neurotic depression. The research method used is library research by analyzing books by Dadang Hawari. Psychoreligious therapy is a treatment that contains religious elements in healing individuals through a psychological approach that is able to build confidence in themselves and a sense of optimism in patients through prayer, dhikr and prayer. The provision of this therapy can have an influence in reducing neurotic depression by relaxing the individual in bringing the individual to peace of mind to create a sense of happiness and focusing the individual in restoring lost consciousness in the nervous system and having a positive impact on individual mental health